Abd al-Rahman al-Kawākibī dan Visi Politik Islam - Nabil Amir, Ahmad; Rahman, Tasnim Abdul (Tebuireng: Journal of Islamic Studies and Society, 2023)
The paper address the political view of ‘Abd al-Rahmān b. Ahmad al-Kawākibī (1855- 1902) in the context of historical tradition and political structure of the Ottoman caliphate in the late 19th century. It looks into his critics of dictatorial rule and oppressive system of the caliphate and its call for the dismantling of the unjust and tyrannical framework. The study is based on qualitative method and documentary approach. The data obtained from reliable library material and source in the form of manuscript, dissertation, book, newspaper and magazine. The information derived is analysed using descriptive, analytical, comparative, and historical method. The finding shows that al-Kawakibi’s underlying philosophy and movement has largely influenced the Arab consciousness of the Middle East in the late 19th century, inspiring revolutionary ideas and movement in the East Mediterranean toward meaningful political liberation and the formation of nation state, bringing the spirit of nationalism and enlightenment throughout the Arab world.